2016
DOI: 10.1093/mnras/stw3369
|View full text |Cite
|
Sign up to set email alerts
|

A simple and general method for solving detailed chemical evolution with delayed production of iron and other chemical elements

Abstract: We present a theoretical method for solving the chemical evolution of galaxies, by assuming an instantaneous recycling approximation for chemical elements restored by massive stars and the Delay Time Distribution formalism for the delayed chemical enrichment by Type Ia Supernovae. The galaxy gas mass assembly history, together with the assumed stellar yields and initial mass function, represent the starting point of this method. We derive a simple and general equation which closely relates the Laplace transfor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 60 publications
1
14
0
Order By: Relevance
“…The yield for delayed metals is adopted to be y ∆ Z ≈ 2.7 × 10 −3 ; this has been computed taking into account that the occurrence of type-Ia SNe is around 2 × 10 −3 /M per stellar mass formed, and that 0.63 M of iron-group elements are produced on average per explosion (see Bell et al 2003;Maoz et al 2014); the outcome is also consistent with the normalization of the observed type-Ia SN delay time distribution (e.g., Vincenzo et al 2017).…”
Section: Yields and Other Imf-related Parameterssupporting
confidence: 65%
See 1 more Smart Citation
“…The yield for delayed metals is adopted to be y ∆ Z ≈ 2.7 × 10 −3 ; this has been computed taking into account that the occurrence of type-Ia SNe is around 2 × 10 −3 /M per stellar mass formed, and that 0.63 M of iron-group elements are produced on average per explosion (see Bell et al 2003;Maoz et al 2014); the outcome is also consistent with the normalization of the observed type-Ia SN delay time distribution (e.g., Vincenzo et al 2017).…”
Section: Yields and Other Imf-related Parameterssupporting
confidence: 65%
“…Finally, some specific issues related to the global evolution of the baryonic content in galaxies can be tackled with analytic models, i.e., models with analytic solutions (e.g., Schmidt 1963;Talbot & Arnett 1971;Tinsley 1974;Pagel & Patchett 1975;Hartwick 1976;Chiosi 1980;Matteucci & Greggio 1986;Edmunds 1990;Dwek 1998;Hirashita 2000, Hirashita et al 2015Chiappini et al 2001;Draine 2003Draine , 2011Inoue 2003;Greggio 2005;Naab & Ostriker 2006;Erb 2008;Zhukovska et al 2008;Valiante et al 2009;Bouché et al 2010;Dwek & Cherchneff 2011;Davé et al 2012;Asano et al 2013;Lilly et al 2013;De Benassutti et al 2014;Dekel & Mandelker 2014;Forbes et al 2014a;Pipino et al 2014;Feldmann 2015;Mancini et al 2015;Mollá et al 2015;Recchi & Kroupa 2015;Rodriguez-Puebla et al 2016;Andrews et al 2017;Gioannini et al 2017;Spitoni et al 2017;Weinberg et al 2017;Vincenzo et al 2017;Grisoni et al 2018;Imara et al 2018;…”
mentioning
confidence: 99%
“…This is due to the fact that Type II SNe trace the SFR. If the SFR peaks at early time (e.g., τ D1 =0.1), at t max = 4.3 Gyr the iron produced by Type Ia SNe with a time delay will dominate the ISM pollution (Matteucci et al 2009;Bonaparte et al 2013;Vincenzo et al 2017). When the SFR is more extended in time (e.g., τ D1 =2), a smaller [α/Fe] abundance ratio is therefore expected.…”
Section: Model Results Taking Into Account the Observational Errorsmentioning
confidence: 99%
“…Côté et al (2017) and Andrews et al (2017) both assume a linear Schmidt law n Schmidt = 1 (same as this work), whereas Chiappini et al (2001) use n Schmidt = 1.5 together with a gas density threshold. See Vincenzo et al (2017) for a detailed comparison between linear and non-linear Schmidt law. …”
Section: Stellar Physics Parametersmentioning
confidence: 99%